Seedling Establishment and Forage Accumulation of ’Ceres Tonic’ Plantain in Pure Stands and in Grass Mixtures - Cid,M. Silvia (Instituto de Investigaciones Agropecuarias, INIA, 2011)
This study evaluates the balance of species 2 mo after sowing, its effects on seasonal and annual dry matter accumulation of Plantago lanceolata L. ’Ceres Tonic’ sown in pure stands, in binary mixtures with three grasses, and different initial growth rates: annual ryegrass (Lolium multiflorum Lam.), tall fescue (Festuca arundinacea Schreb.), and orchard grass (Dactylis glomerata L.). Plantain monocultures were sown at three densities (4, 8, and 12 kg seed ha-1), while halved densities were used in the mixtures. Each grass was sown at the density that is typical for the region (annual ryegrass = 30, tall fescue = 15, and orchard grass = 6 kg seed ha-1). The trial was carried out in Balcarce (37°45’ S, 58°18’ W; 130 m.a.s.l.), Argentina in 1.4 × 5 m plots sown in April 2005 with a randomized complete block design, a factorial arrangement of pasture type and plantain sowing density, and seasons as a measurement repeated over time. Plant density 2 mo after sowing was not a good estimator of the balance between species for all pasture types at the end of the first year. Total forage accumulation throughout the experimental period was affected by pasture type (p = 0.08) and plantain sowing density (p < 0.05), but not by their interaction (p > 0.05). The plantain and annual ryegrass mixture accumulated 28% more biomass than the mean biomass of all the other pastures (7948 ± 647 vs. 6204 ± 502 kg DM ha-1) mainly because of its higher yield in fall and winter. Total precipitation during the year under study was 15% lower than the historic average so that higher accumulations could be expected in years with higher precipitation.